Financial Inclusion (FI) Through Digitization- A Review (Trinity Journal of Management, IT & Media (TJMITM), 2016)
Each and every five year plan, the priority for the nation has been  its economic growth, education for all and financial inclusion  for the vast population of the country. While India has made  some noteworthy progress in the past six and half decades and  more, but on the aspect of financial inclusion, progress has not  been satisfactory. According to census 2011, out of 24.67 crore  households in India, only about 14.48 crore (58.70 %) households  had access to banking services. Further, of the 16.78 crore rural  households, only about 9.14 crore (54.46 %) households were  availing of banking services.” “The World Bank Findex Survey  (2012) points out that only about 35% of Indian adults had access  to a formal bank account and a meager 8% borrowed formally in  the last 12 months,” The question now is do we can either continue  with our traditional ways of ensuring financial inclusion or look at  new methods and opportunities that is available to us because of  technology? India has made rapid strides in technology and it is  important to now look at financial inclusion through the prism of  the digital economy. The government of India has taken initiative  to digitize services that made available to citizens electronically  by improving online infrastructure and by increasing Internet  connectivity.
Keywords: economic growth; financial inclusion; Indian adults; infrastructure